2016
DOI: 10.1177/2333721416677469
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Retention

Abstract: Objectives: The objectives of this study were to evaluate the capability of a research volunteer registry to retain community-dwelling African American older adults, and to explore demographic and health factors associated with retention. Method: A logistic regression model was used to determine the influence of demographics, health factors, and registry logic model activities on retention in a sample of 1,730 older African American adults. Results: Almost 80% of participants active in the volunteer research r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…First, more than 100 participants were directly recruited from the Healthier Black Elders Participant Registry, which is part of the University of Michigan-Wayne State University NIA P30 Resource Center for Minority Aging Research. This required additional approval from the Healthier Black Elders Community Advisory Board (see Hall et al, 2016, for details on recruitment and retention of registry members). Second, the first author gave a number of presentations to groups of older adults across a wide variety of locations and settings (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…First, more than 100 participants were directly recruited from the Healthier Black Elders Participant Registry, which is part of the University of Michigan-Wayne State University NIA P30 Resource Center for Minority Aging Research. This required additional approval from the Healthier Black Elders Community Advisory Board (see Hall et al, 2016, for details on recruitment and retention of registry members). Second, the first author gave a number of presentations to groups of older adults across a wide variety of locations and settings (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Selecting a sample of participants from an existing research registry helped to more quickly establish trust and rapport, as participants were aware that only researchers with approved and vetted studies through the registry would have access to their contact information for research purposes. Many registry participants were accustomed to and comfortable with phone-based research participation due to advanced age, lack of transportation, and flexibility in scheduling (Hall et al, 2016). Participants provided verbal consent over the phone to be interviewed and recorded by phone; participants’ consent was audio-recorded.…”
Section: Methodsmentioning
confidence: 99%
“…Still, researchers across the biomedical and socio-behavioral health spectrum continue to report challenges in implementing the types of community outreach, partnership, and trust-building that are necessary to recruit and retain African American research participants to their studies. [13][14][15][16] The Michigan Center for Urban African American Aging Research (MCUAAAR) has demonstrated success with recruiting and retaining thousands of older African Americans into research studies 17,18 by fostering an active community advisory board (CAB), engaging in frequent and targeted community outreach, and partnering with stakeholders invested in the health of African American older adults. Our objective for this article is to describe these strategies with an emphasis on the defining role that the CAB plays as gatekeepers of community-engaged research efforts.…”
Section: Role Of Community Advisory Board In Research -Mitchell Et Almentioning
confidence: 99%